In vitro and in vivo evaluation of whey protein hydrogels for oral delivery of riboflavin. (December 2015) - O'Neill, Graham J.; Jacquier, Jean Christophe; Mukhopadhya, Anindya; Egan, Thelma; O'Sullivan, Michael; Sweeney, Torres; O'Riordan, E. Dolores
Highlights: Riboflavin release from wet microbeads in vitro was rapid. Convection drying significantly slowed the release rate in vitro . Dried microbeads showed excellent resistance to in vivo digestion. Abstract: The release of riboflavin from whey microbeads under in vitro and in vivo gastrointestinal conditions was evaluated. Release of riboflavin from whey protein microbeads subjected to in vitro gastric digestion was rapid. To limit the release of riboflavin the microbeads were convection dried at 30 °C. Effects of temperature, pH and simulated gastric salts on the release of riboflavin from dried beads were examined. Dried microbeads underwent swelling at gastric and intestinal pH resulting in the release of 58 and 34% of riboflavin respectively in the first hour. Drying significantly decreased the riboflavin release rate constant ( k r ) from 0.1 to 0.016/min. Microbeads fed to piglets via oral gavage showed good resistance to gastrointestinal degradation as microbeads recovered from the colon 8.5 hours after ingestion were only partially degraded. This study showed that dried whey microbeads have potential as an encapsulation system for oral delivery of bioactives to the intestine.